P05.93 Adult medulloblastoma: analysis of use of chemotherapy in clinical practice. (19th September 2018) - Mastall, M; Majd, N; Fuller, G; Gule-Monroe, M; Huse, J; Khatua, S; Rao, G; Sandberg, D; Wefel, J; Yeboa, D; Zaky, W; Mahajan, A; et al.
Abstract: BACKGROUND: Adult medulloblastoma (MB) is rare, accounting for 150–300 new cases in the US annually. Given the low incidence, prospective studies are challenging, and the role of adjuvant chemotherapy in standard risk patients has been controversial. Currently, the best evidence available (Level V) supports the use of upfront chemotherapy. A recent pilot prospective study (NOA-07) proved feasibility of craniospinal irradiation with vincristine, followed by cisplatin, lomustine and vincristine; 4 cycles were feasible in most patients. However, toxicity was substantial. In clinical practice, attempts to ameliorate the intensity of the treatment regimen are common, such as substitution of cisplatin by carboplatin, or removal of vincristine. It is not known if these modifications compromise outcome, and the optimal chemotherapy regimen for adult MB patients to balance efficacy and tolerability has not been established. Methods: We analyzed patterns of use of chemotherapy retrospectively in a large single institution database of patients with adult medulloblastoma. To date, 136 patients (≥18 years at diagnosis) evaluated from January 1978 to April 2017 have been identified (additional patients are being analyzed). Median progression-free survival (mPFS), median overall survival (mOS), 5-year progression free survival (PFS-5) and 5 year-overall survival (OS-5) were estimated using the Kaplan-Meier method. Results: Median age was 28 (18–63); female-to-male ratio 1.7:1; 69/136 (50.7%) were standard risk, and 53/136 (39.0%) were high risk (subtotal resection and/or metastasis) (indeterminate risk in 14). In patients without residual disease at initial diagnosis, 27/79 (34.2%) received chemotherapy upfront; carboplatin vs. cisplatin regimens in 8 vs. 11 patients; vincristine vs non-vincristine in 20 vs. 6 patients. The patients treated with upfront chemotherapy had significant improvement in outcome in comparison with those who did not receive upfront chemotherapy (PFS-5 of 56.6% vs. 84.2%, p=0.018 and OS-5 of 79.5% vs. 90.0%, p=0.050). There was no statistically significant difference between the survival of those who had received carboplatin vs. cisplatin (PFS-5 of 100% vs. 74.1%, p=0.197 and OS-5 of 100% vs. 85.7%, p=0.325). Addition of vincristine was not associated with improved outcome (PFS-5 92.9% vs. 55.6%, p=0.166 and OS-5 of 90.9% vs. 83.3%, p=0.090). Conclusion: To date, we have not found a statistically significant difference in outcome in patients without residual disease treated with carboplatin vs. cisplatin-based regimens, or between regimens containing vincristine and regimens not containing vincristine. Attenuated regimens of chemotherapy in adult medulloblastoma patients may decrease toxicity without compromising efficacy. Additional patients will be added to this cohort to further improve the accuracy of this study.